2005
DOI: 10.1192/bjp.187.5.450
|View full text |Cite
|
Sign up to set email alerts
|

Reality orientation therapy combined with cholinesterase inhibitors in Alzheimer's disease: randomised controlled trial

Abstract: Reality orientation enhances the effects of donepezil on cognition in Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
182
3
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(199 citation statements)
references
References 26 publications
(30 reference statements)
11
182
3
2
Order By: Relevance
“…Its objective is creating environmental stimuli that have eased the temporal and spatial orientation of the patient 83 . other technique employed in this same approach is the reminiscent therapy (RT).…”
Section: Feedback Role In Ad Patients' Performancementioning
confidence: 99%
“…Its objective is creating environmental stimuli that have eased the temporal and spatial orientation of the patient 83 . other technique employed in this same approach is the reminiscent therapy (RT).…”
Section: Feedback Role In Ad Patients' Performancementioning
confidence: 99%
“…The other studies did not provide information regarding where groups were held. 49,51,53 All of the studies reported on attrition to the programme, although the intention-to-treat analysis plan was described in only two. 6,51 Given the nature of the condition and the age of the participants, attrition in several studies was remarkably small, with zero attrition recorded in six studies [48][49][50]52,59,60 out of 180 participants.…”
Section: Figurementioning
confidence: 99%
“…47 Two reviewers independently assessed eligibility. Of the 94 references, nine studies met the inclusion criteria [48][49][50][51][52][53][54][55] and were included in the analysis. Three recent studies were left awaiting classification.…”
Section: Studies Included In the Reviewmentioning
confidence: 99%
See 2 more Smart Citations